2009
DOI: 10.1007/s00192-009-0866-1
|View full text |Cite
|
Sign up to set email alerts
|

Incontinence pessaries: size, POPQ measures, and successful fitting

Abstract: Introduction and hypothesisThe aim of the study was to determine whether successful incontinence pessary fitting or pessary size can be predicted by specific POPQ measurements in women without advanced pelvic organ prolapse.MethodsIn a multicenter study, women with stress urinary incontinence (SUI) and POPQ stage ≤2 were randomized to three treatment arms: (1) incontinence pessary, (2) behavioral therapy, or (3) both. This study evaluates incontinence pessary size, POPQ measures, and successful fitting in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 15 publications
0
20
1
2
Order By: Relevance
“…Nager et al found that women with a longer vagina are more likely to be fitted successfully but that various formulas including the TVL do not predict pessary size [9]. However, our findings showed that the ring pessary with support is round, and if the pessary is retained in the vagina, then the TVL and vaginal introitus width are both factors determining pessary size.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…Nager et al found that women with a longer vagina are more likely to be fitted successfully but that various formulas including the TVL do not predict pessary size [9]. However, our findings showed that the ring pessary with support is round, and if the pessary is retained in the vagina, then the TVL and vaginal introitus width are both factors determining pessary size.…”
Section: Discussioncontrasting
confidence: 71%
“…Fitting a pessary is currently guided by experience [4]. There is no consensus on clinical indications for the various types of pessaries or the patient characteristics for sizing [9]. Many providers fit pessaries.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the overall POP‐Q stage and predominant prolapse compartment, other pelvic examination parameters, including TVL, vaginal introitus and genital hiatus (GH), were also evaluated as risk factors for an unsuccessful pessary fitting trial. Unsuccessfully fitted patients had a shorter vaginal length and wider vaginal introitus . Several studies employed extreme values of the pelvic examination parameters to predict unsuccessful pessary fitting, but the cut‐off values were inconsistent among these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Unsuccessfully fitted patients had a shorter vaginal length and wider vaginal introitus. 12,25 Several studies employed extreme values of the pelvic examination parameters to predict unsuccessful pessary fitting, but the cut-off values were inconsistent among these studies. A shorter vaginal length (≤ 7, ≤ 6 or < 6 cm), 12,23,26 wider vaginal introitus (> 4 fingerbreadths), 12,26 and greater GH/ TVL ratio (≥ 0.9) 19,23 were reported to be associated with an unsuccessful fitting.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested by other authors that previous prolapse surgery or hysterectomy narrows the upper vaginal diameter, making it difficult to retain a pessary [19,20]. It is likely that .…”
Section: Risk Factors For Discontinuationmentioning
confidence: 99%